Association of soil fungal community composition with incidence of Fusarium wilt of banana in Malaysia - Jamil, Fatin Nadiah; Hashim, Amalia Mohd; Yusof, Mohd Termizi; Saidi, Noor Baity (Taylor and Francis, 2023)
Banana (Musa spp.), an important food crop in many parts of the world, is threatened by a deadly wilt disease caused by Fusarium oxysporum f. sp. cubense Tropical Race 4 (TR4). Increasing evidence indicates that plant actively recruits beneficial microbes in the rhizosphere to suppress soil-borne pathogens. Hence, studies on the composition and diversity of the root-associated microbial communities are important for banana health. Research on beneficial microbial communities has focused on bacteria, although fungi can also influence soil-borne disease. Here, high-throughput sequencing targeting the fungal internal transcribed spacer (ITS) was employed to systematically characterize the difference in the soil fungal community associated with Fusarium wilt (FW) of banana. The community structure of fungi in the healthy and TR4-infected rhizospheres was significantly different compared with that of bulk soil within the same farm. The rhizosphere soils of infected plants exhibited higher richness and diversity compared with healthy plants, with significant abundance of Fusarium genus at 14. In the healthy rhizosphere soil, Penicillium spp. were more abundant at 7 and positively correlated with magnesium. This study produced a detailed description of fungal community structure in healthy and TR4-infected banana soils in Malaysia and identified candidate biomarker taxa that may be associated with FW disease promotion and suppression. The findings also expand the global inventory of fungal communities associated with the components of asymptomatic and symptomatic banana plants infected by TR4.